2014
DOI: 10.3945/ajcn.114.088500
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations of television, electronic games, and digital versatile discs with changes in diet in adolescents

Abstract: Increases in screen time were associated with increased consumption of foods and beverages of low nutritional quality and decreased consumption of fruit and vegetables. Our results caution against excessive use of screen media, especially television, in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 64 publications
10
69
0
13
Order By: Relevance
“…Time-varying MVPA was positively associated with more favorable timevarying HEI and WPF scores, consistent with previous studies showing positive associations of self-reported physical activity with several aspects of better dietary intake in adolescents and older adults (46,47). Similarly, the inverse relations of television viewing with all diet quality indicators and of gaming with HEI and EC in this study are consistent with 2 prospective studies that reported inverse associations of these behaviors with aspects of diet quality (e.g., intake of fruits and vegetables, fast food, sugarsweetened beverages, and energy-dense snacks) (44,48). To our knowledge, the association of diet quality with social networking and other Internet use has not been examined previously.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Time-varying MVPA was positively associated with more favorable timevarying HEI and WPF scores, consistent with previous studies showing positive associations of self-reported physical activity with several aspects of better dietary intake in adolescents and older adults (46,47). Similarly, the inverse relations of television viewing with all diet quality indicators and of gaming with HEI and EC in this study are consistent with 2 prospective studies that reported inverse associations of these behaviors with aspects of diet quality (e.g., intake of fruits and vegetables, fast food, sugarsweetened beverages, and energy-dense snacks) (44,48). To our knowledge, the association of diet quality with social networking and other Internet use has not been examined previously.…”
Section: Discussionsupporting
confidence: 80%
“…This study extends the literature on behavioral correlates of diet quality by examining a broad range of time-varying lifestyle behaviors and diet-quality indicators during an understudied developmental stage. Findings largely confirm those from previous studies showing associations of aspects of better diet quality with more frequent breakfast (8,18) and family meals (40) and with less frequent television viewing during meals (41,42), eating at fast-food restaurants (17,43), and overall television viewing (11,42,44,45). The consistency of these associations across a variety of age groups supports the plausibility of causality between the variables, although controlled intervention trials are necessary to confirm these observational findings.…”
Section: Discussionsupporting
confidence: 79%
“…However, our results showed an adverse impact of game-playing, but not TV viewing on toothbrushing frequency. One of the strongest risk factors for dental caries is sugar consumption (Kalsbeek and Verrips 1994), and snacking is reportedly more distinct during TV viewing than game playing (Falbe et al 2014). Moreover, larger amounts of snacking are not necessarily associated with a higher frequency of toothbrushing (Peltzer and Pengpid 2014).…”
Section: Discussionmentioning
confidence: 99%
“…14 TV viewing is a risk factor for weight gain, 15,16 decreased academic achievement, and behavioral problems. 15 Although there is ample evidence that food marketing mediates the TV-obesity relationship, [17][18][19][20] sleep may also mediate this relationship and others. Possible mechanisms include direct displacement of screen time for sleep, increased cognitive and emotional arousal, and delays in circadian rhythm from screen light.…”
Section: What This Study Addsmentioning
confidence: 99%